Penile Invasive Squamous Cell Carcinoma: Analysis of Incidence, Mortality Trends, and Geographic Distribution in Canada. Issue 2 (March 2020) - Lagacé, François; Ghazawi, Feras M.; Le, Michelle; Savin, Evgeny; Zubarev, Andrei; Powell, Mathieu; Moreau, Linda; Sasseville, Denis; Popa, Ioana; Litvinov, Ivan V.
Background: Penile invasive squamous cell carcinoma (SCC) is a rare disease with several known risk factors. However, few studies have assessed its incidence, mortality, and temporal trends. Objective: Our objectives are to analyze the epidemiology of penile SCC in Canada and to examine patient distribution with this cancer across Canada in order to elucidate population risk factors. Methods: Three independent cancer registries were used to retrospectively analyze demographic data from Canadian men diagnosed with penile invasive SCC between 1992 and 2010. The Canadian Census of Population was used to calculate incidence and mortality rates at the province and Forward Sortation Area levels. Results: The overall age-adjusted incidence rate was 6.08 cases per million males. Four provinces with statistically significantly higher incidence rates were identified. The national crude incidence rates increased linearly between 1992 and 2010, whereas the age-adjusted incidence rates showed no significant increase during this time period. The overall age-adjusted mortality rate was 1.88 deaths per million males per year. The province of Saskatchewan had significantly higher mortality rates. There was no increase in crude or age-adjusted mortality rates between 1992 and 2010. There was a significant positive correlation between incidence rates and obesity, Caucasian ethnicity, and lower socioeconomic status. Conclusion: This study was able to establish geographic variation for this malignancy at the provincial level. Although there are many established risk factors for penile SCC, our results suggest that the increase in crude incidence rates observed is largely due to the aging population.